Review of old chemistry and new catalytic advances in the on-purpose synthesis of butadiene - Makshina, Ekaterina V; Dusselier, Michiel; Janssens, Wout; Degrève, Jan; Jacobs, Pierre A; Sels, Bert F (Chemical Society reviews, 2014)
Increasing demand for renewable feedstock-based chemicals is driving the interest of both academic and industrial research to substitute petrochemicals with renewable chemicals from biomass-derived resources. The search towards novel platform chemicals is challenging and rewarding, but the main research activities are concentrated on finding efficient pathways to produce familiar drop-in chemicals and polymer building blocks. A diversity of industrially important monomers like alkenes, conjugated dienes, unsaturated carboxylic acids and aromatic compounds are thus targeted from renewable feedstock. In this context, on-purpose production of 1,3-butadiene from biomass-derived feedstock is an interesting example as its production is under pressure by uncertainty of the conventional fossil feedstock. Ethanol, obtained via fermentation or (biomass-generated) syngas, can be converted to butadiene, although there is no large commercial activity today. Though practised on a large scale in the beginning of the 20th century, there is a growing worldwide renewed interest in the butadiene-from-ethanol route. An alternative route to produce butadiene from biomass is through direct carbohydrate and gas fermentation or indirectly via the dehydration of butanediols. This review starts with a brief discussion on the different feedstock possibilities to produce butadiene, followed by a comprehensive summary of the current state of knowledge regarding advances and achievements in the field of the chemocatalytic conversion of ethanol and butanediols to butadiene, including thermodynamics and kinetic aspects of the reactions with discussions on the reaction pathways and the type of catalysts developed.